2013
DOI: 10.11566/cmoshmcj.v12i2.38
|View full text |Cite
|
Sign up to set email alerts
|

Choledocholithotomy without T tube Drainage: Our Initial Experience

Abstract: Introduction: Gallstone disease occurs in 3%-20% of the world population and about 15% of people with gallstone disease develop stones in the common bile duct (CBD). Smaller stones are amenable to be removed by endoscopic retrograde cholangio-pancreatography (ERCP) while larger stones require surgery-either open or by laparoscopic. Materials and Methods: This was a prospective study between January 2010 and December 2012 in two hospitals in Chittagong, Bangladesh, on ultrasonography upper abdomen. And where ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Conventionally after CBD exploration T tube is placed after bile duct exploration and the logic behind this technique is that it allows spasm or edema of sphincter to settle after the trauma of the exploration and T-tube drainage has been used to prevent bile stasis, decompress the biliary tree, and minimize the risk of bile leakage moreover it also provides an easy percutaneous access for cholangiography and extraction of retained stones. 15 However studies [16][17][18][19][20][21][22] are available in literature that now favor choleduchotomy and primary choledochorrhaphy instead of conventional T tube placement method in order avoid its associated complications. Our study showed no major morbidity and no mortility after primary repair of common bile duct after supraduodenal choledochotomy followed by its closure without placement of T tube.…”
Section: Discussionmentioning
confidence: 99%
“…Conventionally after CBD exploration T tube is placed after bile duct exploration and the logic behind this technique is that it allows spasm or edema of sphincter to settle after the trauma of the exploration and T-tube drainage has been used to prevent bile stasis, decompress the biliary tree, and minimize the risk of bile leakage moreover it also provides an easy percutaneous access for cholangiography and extraction of retained stones. 15 However studies [16][17][18][19][20][21][22] are available in literature that now favor choleduchotomy and primary choledochorrhaphy instead of conventional T tube placement method in order avoid its associated complications. Our study showed no major morbidity and no mortility after primary repair of common bile duct after supraduodenal choledochotomy followed by its closure without placement of T tube.…”
Section: Discussionmentioning
confidence: 99%
“…15 However studies [16][17][18][19][20][21][22] are available in literature that now favor choleduchotomy and primary choledochorrhaphy instead of conventional T tube placement method in order avoid its associated complications. Our study showed no major morbidity and no mortility after primary repair of common bile duct after supraduodenal choledochotomy followed by its closure without placement of T tube.…”
Section: Table-ii Frequency Of Complications (N = 24)mentioning
confidence: 99%